Atmospheric Parameters and Luminosities of Nearby M Dwarfs – Estimating Habitable Exoplanet Detectability with the E-ELT. Issue Volume 12:Issue S328(2016) (12th September 2017) - Porto de Mello, Gustavo F.; Giribaldi, Riano E.; Lorenzo-Oliveira, Diego; Leme, Nathália M. Paes
Abstract: We derive T eff and [Fe/H] for a sample of 72 nearby M-dwarfs with Hipparcos parallaxes and δ < +30. Spectra, acquired at the Observatório do Pico dos Dias, Brazil, have R = 10, 000 and S/N ≳ 100 for nearly all targets in the λλ8380-8880 range. Atmospheric parameters were derived from VJHK colors and a system of spectral line indices calibrated against sample stars with interferometric T eff and [Fe/H] from detailed analysis of FGK binary companions. A PCA method of calibration yields internal errors within 70 K and 0.1 dex for T eff and [Fe/H]. For 18 stars we present the first T eff or [Fe/H] derivation in the literature. We compute the star's luminosities, calculate the position of their habitable zones and estimate that, were all of they to harbour rocky planets inside their HZ, 15–20 of these would be detectable by the E-ELT Planetary Camera and Spectrograph.